Loyalitas Nasabah Bank Nagari Syariah Cabang Bukittinggi Dilihat dari Kualitas Pelayanan - Doni Marlius (JURNAL PUNDI, 2017)
Customer loyalty is very important for companies that maintain the continuity of their business and the continuity of business activities. The purpose of this study is to determine the effect of service quality on customer loyalty Bank Syariah Bank Bukittinggi Branch. The sample used counted 86 people, with method of doubled linear regression analysis. The result proves that the physical evidence has a significance value of 0.016 <0.05, empathy has a significance value of 0.023 <0.05, reliability has a significance value of 0.014 <0.05, the responsiveness has a significance value of 0.000 <0.05, the assurance has a value significance of 0.174> 0.05, that physical evidence, empathy, reliability, responsiveness and assurance have a significance value of 0,000 <0.05. Thus the physical evidence, empathy, reliability, responsiveness and collateral together have a positive and significant impact on customer loyalty of Bank Nagari Syariah Bukittinggi Branch.Keywords: Loyalty, Quality of Service